Comparison of in vivo kinematic and radiological parameters of three cervical disc prostheses - Nicholas Chang; Ralph Mobbs; Nicholas Hui; Henry Lin (Journal of Craniovertebral Junction and Spine, 2022)
Introduction: Cervical total disc replacement (CTDR) is an alternative to anterior cervical discectomy and fusion for select patients that may preserve range of motion and reduce adjacent segment disease. Various CTDR prostheses are available; however, comparative data are limited. This study aimed to compare the short-term kinematic and radiological parameters of the M6-C, Mobi-C, and the CP-ESP prostheses. Methods: This retrospective cohort study included patients treated with CTDR between March 2005 and October 2020 at a single institution. Patients were included if their follow-up assessment included lateral erect and flexion/extension radiographs. The primary outcome assessed at 3-months postoperatively was range of motion, measured by the difference in functional spinal unit angle between flexion and extension. Results: A total of 131 CTDR levels (120 patients, 46.2 ± 10.1 years, 57% male) were included. Prostheses implanted included the M6-C (n = 52), Mobi-C (n = 54), and CP-ESP (n = 25). Range of motion varied significantly (8.2° ± 4.4° vs. 10.9° ± 4.7° vs. 6.1° ± 2.7°, P < 0.001). On post hoc analysis, the Mobi-C prosthesis demonstrated a significantly greater range of motion than either the M6-C prosthesis (P = 0.003) or CP-ESP (P < 0.001). Conclusion: Although the optimal range of motion for CTDR has not been established, short-term differences in the range of motion may guide the selection of CTDR prosthesis. Further studies with longer follow-up and consideration of clinical outcome measures are necessary.